Characterisation of the phase-transformation behaviour of Ce2O(CO3)2·H2O clusters synthesised from Ce(NO3)3·6H2O and urea. Issue 1 (21st November 2014) - D'Angelo, Anita M.; Webster, Nathan A. S.; Chaffee, Alan L.
<x content-type="archive" xml:space="preserve">Abstract</x> X-ray diffraction (XRD) was used to determine the temperature at which the transformation of Ce2O(CO3)2·H2O to ceria (CeO2) occurs under both a flow of nitrogen and air as a function of temperature. The Ce2O(CO3)2·H2O synthesised from Ce(NO3)3·6H2O and urea was further investigated using thermal gravimetric analysis (TGA), scanning electron microscopy (SEM), and transmission electron microscopy (TEM). XRD results indicate that, under a flow of nitrogen, CeO2 is formed at temperatures greater than 500 °C and that this occurs via an as yet unidentified intermediate phase, which is present between 430 and 540 °C. Results obtained by the XRD correspond to those obtained using TGA, which show weight losses commencing at 430 and at 465 °C. No further weight loss occurs above 540 °C, because of the formation of CeO2 as the stable product. The crystallite size was also determined and observed to increase with increasing temperature. Under a flow of air the transformation occurred at a lower temperature, as CeO2 was formed at 250 °C. SEM and TEM reveal the particles have a rod-shaped morphology which is retained after calcination. These results may be used to optimise synthesis methods to minimise crystallite size growth and reduce sintering that is undesirable in many applications, particularly catalysis.